Arginase–endothelial nitric oxide synthase imbalance contributes to endothelial dysfunction during chronic intermittent hypoxia. Issue 3 (March 2015) - Krause, Bernardo J.; Del Rio, Rodrigo; Moya, Esteban A.; Marquez-Gutierrez, Monica; Casanello, Paola; Iturriaga, Rodrigo
<x xml:space="preserve">Abstract</x> Objective: Chronic intermittent hypoxia (CIH), the main feature of obstructive sleep apnoea, is associated with impaired vascular function despite unaltered response to nitric oxide donors. This study addressed whether arginase contributes to the endothelial dysfunction in CIH rats. Methods: Adult male Sprague–Dawley rats were exposed for 21 days to CIH (5% oxygen, 12 times/h, 8 h/day). The internal carotid arteries were isolated to study endothelial nitric oxide synthase (eNOS) and arginase-1 levels by western blot and immunohistochemistry, and their vasoactive responses using wire myography. Relaxation to sodium nitroprusside (SNP; nitric oxide donor) in the presence or absence of soluble guanylyl cyclase inhibitor, and acetylcholine with and without a NOS inhibitor [NG-nitro-L-arginine (L-NA)] and the arginase inhibitor BEC were determined. Results: Arteries from the CIH rats presented higher active contraction induced by KCl (3.5 ± 0.4 vs. 2.3 ± 0.2 N/m2), augmented media-to-lumen ratio (∼40%), decreased relaxation to acetylcholine (12.8 ± 1.5 vs. 30.5 ± 4.6%) and increased sensitivity to SNP (pD2 7.3 ± 0.1 vs. 6.7 ± 0.1). Arginase inhibition reversed the impaired acetylcholine-induced relaxation in CIH arteries (49.5 ± 7.4%), an effect completely blocked by L-NA. In the carotid arteries, arginase-1 protein level was increased, whereas eNOS levels decreased in the CIH arteries. Conclusion: The current results suggest that endothelial dysfunction in CIH-induced hypertension may result from imbalanced arginase-1 to eNOS expression, vascular remodelling and increased contractile capacity, rather than decreased vascular response to nitric oxide.